2D-metal–organic coordination polymers of lanthanides (La(iii), Pr(iii) and Nd(iii)) with redox-active dioxolene bridging ligands. Issue 28 (8th July 2020) - Kharitonov, Alexandr D.; Trofimova, Olesya Y.; Meshcheryakova, Irina N.; Fukin, Georgy K.; Khrizanforov, Mikhail N.; Budnikova, Yulia H.; Bogomyakov, Artem S.; Aysin, Rinat R.; Kovalenko, Konstantin A.; Piskunov, Alexandr V.
Abstract : 2D-coordination redox-active networks bearing t -Bu-substituted anilic bridged ligands and lanthanide ions were synthesized and characterized. Abstract : The synthesis, crystal structure, thermal stability, porosity and magnetic properties of three new layered coordination polymers [(M2 ( p Q)3 )·4DMAA] n (M 3+ = La 3+ (1 ), Pr 3+ (2 ), Nd 3+ (3 ); p Q 2− – the dianionic form of 2, 5-dihydroxy-3, 6-di- tert -butyl- para -quinone; DMAA = N, N ′-dimethylacetamide) are reported. The coordination polymers obtained were investigated by solid-state electrochemistry which demonstrates multistep one-electron transformations caused by the presence of redox-active dioxolene ligands.